Does physical activity differ between youth with and without intellectual disabilities?. Issue 3 (July 2019) - Stanish, Heidi I.; Curtin, Carol; Must, Aviva; Phillips, Sarah; Maslin, Melissa; Bandini, Linda G.
Abstract: Background: Children and youth with intellectual disabilities (ID) are known to face obstacles to physical activity participation, yet the activity patterns of this population are not well characterized. Objective/Hypothesis: In this study, time spent in moderate to vigorous physical activity (MVPA), type, and frequency of participation in physical activities were assessed in youth with ID and in a comparison group of typically developing (TD) youth. Methods: Weekly participation in MVPA in 38 youth with ID and 60 TD youth was assessed via accelerometry. Participants were also administered an interview about the frequency and type of physical activities they engaged in over the past year. Results: After adjusting for age and sex, youth with ID spent significantly less time in MVPA (33.5 vs. 46.5 min/day, p = 0.03) and were less likely to meet the US Physical Activity Guidelines than TD youth (6% vs. 29%, p = 0.01). Although time in MVPA was lower in youth with ID, females with ID participated in physical activities more frequently than TD females (47.1 vs. 28.2 times/month, p = 0.008) and also reported engaging in a greater variety of physical activities (7.8 vs. 5.2 activities/year, p = 0.01). No differences between males in the frequency of physical activity participation or the number of activities performed were observed. Both groups reported walking/hiking and active video as top activities. Conclusions: Findings emphasize the need for targeted efforts to increase MVPA in youth with ID.